Impact of government expenditure on economic growth in sri lanka during 1980-2017: an econometrics analysis - Joseph Francis, S.; Amirthalingam, K. (University of Jaffna, 2019)
This paper attempts to analyze the relationship between public expenditure and economic growth in Sri Lanka during the period of 1980-2017.Government expenditure is one of the key fiscal policy variables that can influence economic growth in any country. In the short term, counter-cyclical fiscal expansion could boost aggregate demand and growth during cyclical downturns. Economic growth has always been an important yardstick to measure the performance of any economy in the world. This paper intends to investigate the casual relationship between public expenditure (and its components) and economic growthand evaluate short run and long run effects of public expenditure on economic growth in Sri Lanka.Over the decades, it has been noted that the trends and components of public expenditure have undergone significant changes. Annual time series data incorporates five selected components of public expenditure: agriculture, education, health, defense and transport and communication into the model in this study. The study employs secondary annual statistical data for the period starting from 1980 to 2017. Data for the study have been obtained from the annual reports of the Ministry of Finance (MOF) website, annual reports of Central Bank of Sri Lanka (CBSL) and the data bases of Department of Census and Statistics (DCS) and World Bank. All values are expressed in million rupees or as percentages. All variables have been transformed into log form to reduce the problem of heteroskedasticity. Many econometric tools such as ADF unit root test, Johansen Co-integration test, Vector Error Correction modelling and Granger Casualty test to analyze the data. The findings of this study exhibit that effects of fiscal policy on economic growth are complex and varied. Empirical evidence of this study shows that various types of fiscal expenditure have different degrees of impacts on economic growth, implying the existence of a significant potential to improve “growth generating efficiency” of fiscal spending by reallocating expenditures among sectors.
Keywords: Public expenditure; Time series analysis; Economic growth; Growth generating efficiency